A clash of learning cultures? Expatriate TEFL teachers in Brunei Darussalam - Mary F. Nicol, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2008)
There has been concern in recent years over the poor performance of the Cambridge O level English language paper of students in Brunei. Previous investigation of the problem reveals repeated concerns expressed by expatriate EFL teachers over, amongst other issues, a clash of values encountered particularly at the institutional level. This study seeks to uncover the nature of the clash and to consider whether it is an obstacle to improving the English language learning situation in Brunei. A group of expatriate teachers was surveyed and took part in a focus group discussion. The findings suggest that a clash of learning cultures exists, but within the classroom,and is manageable. In contrast, a picture emerges of a more intractable clash at the institutional level, which could be one of the factors hampering the effective learning of English in schools in Brunei.